Contribuições ao estudo de conversores CC–CC com processamento parcial de energia aplicados a sistemas fotovoltaicos - Zientarski, Jonatan Rafael Rakoski (2018)
This work presents some conceptual and practical contributions about the use of series-regulated DC/DC converters in multi-string photovoltaic systems, which have been presented in the literature as capable of performing partial power processing. From a conceptual point of view, the requirements for distinguish which topologies are able or not to perform partial power processing are defined, and for that, it is developed a methodology to evaluate the active and nonactive power processing on the converter, which depend on its design parameters. By means of the analysis of various topologies of series regulators, it is concluded that the partial power processing is achieved by adjusting the duty cycle and the turns ratio of transformers (or coupled inductors). However, because of the voltage gain specifications, not all series regulators topologies cited in the literature are able of operating in the partial power processing region. It is observed that the series regulators based on buck-boost and flyback topologies do not allow to achieve partial energy processing, whereas the series regulators based on forward and full-bridge topologies may perform partial power processing in certain operation ranges. In addition, the application of series regulators in photovoltaic systems allows the use of the input voltage regulation range as an additional parameter to reduce the power processing in the converters. Thus, a methodology was developed to obtain a stochastic model of the voltage profile in which the energy is generated. The methodology employs the mathematical model of the photovoltaic module and historical data of temperature and irradiation, and demonstrates that for each project there is a voltage regulation range of the dc-dc stage that may result in performance improvements in terms of power density and efficiency. From the definition of the voltage regulation range, it has been demonstrated that the use of series regulators based on topologies with bidirectional power flow (acting as both voltage step-up and voltage step-down) allows to reduce the power processing in the converters even further. As an example, the full-bridge/push-pull topology was evaluated, some technical constraints are defined and some advantages and disadvantages of its application are presented. As a result, it is concluded that although voltage step-up/down topologies are more complex, their proper design may result in improvements in efficiency and power density. In order to validate the analyzes, seven 750 W prototypes were built, achieving efficiencies of up to 99.58 %, and power densities up to 4.76 W/cm3.